2016
DOI: 10.1186/s13063-016-1474-2
|View full text |Cite
|
Sign up to set email alerts
|

The experience of adolescents participating in a randomised clinical trial in the field of mental health: a qualitative study

Abstract: BackgroundThis descriptive study aimed to investigate adolescents’ motivations for participating in a randomised controlled trial (RCT), to explore the understanding that the young people had regarding a number of aspects of the trial design, to examine whether or not they found participation in the trial to be acceptable and what affected this, and to identify whether and how the young people felt that their participation in the RCT impacted on their experience of therapy and on therapeutic change.MethodsSeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
(27 reference statements)
1
18
0
Order By: Relevance
“…For example, in a study examining the ethics of general bereavement research, the authors found that bereaved adults felt positive about bereavement research, reporting perceived benefits in line with altruistic motivations [34]. Treatment focused research also suggests that some people are motivated by the hope that research participation will benefit them in personal, direct ways, such as access to treatments [32], a phenomenon termed "conditional altruism" [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study examining the ethics of general bereavement research, the authors found that bereaved adults felt positive about bereavement research, reporting perceived benefits in line with altruistic motivations [34]. Treatment focused research also suggests that some people are motivated by the hope that research participation will benefit them in personal, direct ways, such as access to treatments [32], a phenomenon termed "conditional altruism" [35].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is relevant literature relating to the experience of CYP research participation more generally [38,39], as well as school-based research engagement [31][32][33][34][35] and mental health measure completion for clinical purposes [40]. However, to our knowledge, there is no prior research exploring CYP's experiences of completing mental health and wellbeing measures for school-based research (though a recent study explored school-based completion of self-harm measures [41]).…”
mentioning
confidence: 99%
“…Giving the participants a voice on these central subjects, allowing them to provide their own interpretations of their own experiences and "results" may, as we join the quantitative and qualitative findings together across individuals , give us the strongest handle on what can lead to positive change, and sticking with treatment, or may on the other hand leave the young person still facing what might be a life sentence of disabling depression. So far, papers have addressed the following topics from interviews: the experience of depression (Midgley et al, 2015); where depression has come from ; experience of treatment (Midgley, Holmes, et al, 2016); experience of participating in an RCT (Midgley, Isaacs, Weitkamp, & Target, 2016); and experience of being a parent of a depressed adolescent . Many further questions are to be explored from the very large set of often rich interviews.…”
Section: (6) Finally! Designing and Conducting A Major Randomized Conmentioning
confidence: 99%